Phonetics and phonology. - Apolo Cajamarca, Yhira Johanna (My University, 2019)
This project is aimed at knowing the practical strategies that will help us to articulate the voiceless and voiced sounds in English language. This study will help us to know the difference in the pronunciation of these sounds. The main reference of this research is the experience and the analysis of the vocabulary for an effective and meaningful teaching. It is well known that the English Language presents a certain intonation pattern, even the speed of the speaker seems very similar in certain words with different meanings.The purpose of this important research is to provide teachers appropriate methodological strategies that will help us in the understanding of clear pronunciation in the production of sounds.
Este proyecto está dirigido a conocer las estrategias prácticas que nos ayudará a la articulación de los sonidos sonoros y no sonoros de las consonantes del idioma inglés, estudio que nos ayudará a conocer la diferencia en la pronunciación de fonemas. El referente principal de esta investigación es la experiencia y el análisis del vocabulario para una enseñanza eficaz y significativa ya que el Idioma Inglés presenta cierta entonación, acentuación y hasta la velocidad del hablante muy parecida en ciertas palabras con significado distinto. El propósito de esta importante investigación es proveer a los profesores las estrategias metodológicas adecuadas que ayudarán en la en la comprensión de la pronunciación clara y la producción de los sonidos.
Keywords: ARTICULACION; SONORA; VOZ; FONETICA